THE IMPLEMENTATION OF TRAINING TOWARD THE INCREASE OF VO2MAX IN VOLLEYBALL ATHLETES OF PBV. CAROLINE LUBUKINGGAU CITY - Devi Ratna Sari; Wawan Syafutra; Yuli Febrianti (Fakultas Kedokteran Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to analyze the implementation of interval training to improve the VO2Max of the male volleyball athletes at PBV Caroline, Lubuklinggau City. The research method used quantitative research. Data collection techniques used observation, tests, and documentation. The data analysis technique used the t-test. The results of the study indicate that the application of interval training improves the VO2Max of the male volleyball athletes at PBV Caroline, Lubuklinggau City. This is demonstrated by a significant increase between the pre-test and post-test results, where the athletes' average score experienced a quite high increase after being given the treatment. In addition, the hypothesis test results show that the t-count value and t-table value mean that t-count (4.2492) > t-table (2.790), meaning that Ha is accepted, namely the effect of VO2Max on improving the physical condition of the male volleyball athletes at PBV Caroline, Lubuklinggau City. The conclusion is that the interval training method can be used as a simple, practical, and effective alternative training method to improve the VO2Max of the male volleyball athletes at PBV Caroline, Lubuklinggau City.